Effect of 2% chlorhexidine on microtensile bond strength of composite to dentin - Alves de Castro, Fabrício Luscino [UNESP]; Ferrarezi de Andrade, Marcelo [UNESP]; Duarte Jr., Sillas Luiz Lordello [UNESP]; Vaz, Luis Geraldo [UNESP]; Mendes Ahid, Fernando Jorge [UNESP] (My University, 2003)
Purpose: To evaluate the effect of 2% chlorhexidine on the microtensile bond strength of composite resin to dentin treated with three dentin bonding systems. Materials and Methods: Flat dentinal surfaces were prepared in 24 extracted human third molars. Teeth were randomly divided into 8 distinct experimental groups according to the adhesive applied (Prime & Bond NT, Single Bond and Clearfil SE Bond), the application (yes/no) of chlorhexidine, and the time point at which it was applied (before or after acid etching the dentin). Composite resin blocks were built up over treated surfaces, and teeth were then stored in water at 37°C for 24 h. Samples were thermocycled, stored under the same conditions, and then vertically sectioned, thus obtaining specimens with 1.0 ± 0.1 mm2 cross-sectional area. Specimens were stressed in tension at 0.5 mm/min crosshead speed. Bond strength results were evaluated using a one-way ANOVA (p < 0.05). The modes of failures were verified using optical microscopy. Dentin disks were obtained from 3 additional teeth treated in the same manner for observation under SEM. The most representative samples of fractured specimens were also observed under SEM. Results: No statistically significant differences of bond strength values were found between any groups. Failures occurred mainly within the bond; exclusively adhesive fractures (adhesive-dentin) were not observed. Conclusion: The 2% chlorhexidine solution, applied before or after acid etching of the dentin, did not interfere with the microtensile bond strength of composite resin to the dentin treated with Prime & Bond NT, Single Bond, or Clearfil SE Bond bonding systems.
Keywords: chlorhexidine; dental surgery; mechanical stress; microscopy; molar tooth; tensile strength; tooth fracture; Acid Etching, Dental; Analysis of Variance; Anti-Infective Agents, Local; Bisphenol A-Glycidyl Methacrylate; Chlorhexidine; Composite Resins; Dental Bonding; Dentin-Bonding Agents; Materials Testing; Microscopy, Electron, Scanning; Polymethacrylic Acids; Resin Cements; Surface Properties; Temperature; Tensile Strength; Time Factors